A study to determine the correlation of insulin resistance in pregnancy with obstetric outcomes - Rawat, Aarti; Verma, Monica; Verma, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Insulin resistance (IR) is a physiological adaptation in pregnancy but can predispose to adverse maternal and fetal outcomes if dysregulated. Early identification and monitoring are essential to improve obstetric outcomes and reduce the risk of gestational diabetes mellitus (GDM). Methods: This prospective observational study was conducted at MTH Hospital, Indore, over one year. A total of 200 pregnant women with gestational age up to 26 weeks attending the antenatal clinic were screened for clinical signs of insulin resistance. Those with fasting plasma glucose ≥140 mg/dl or diagnosed with GDM were excluded. Remaining participants were followed up till delivery for obstetric outcomes. Data were collected using a predesigned proforma and analyzed with standard statistical tools. Results: Among the 200 participants, a significant proportion with clinical features of insulin resistance were found to have increased rates of obstetric complications such as preeclampsia, polyhydramnios, preterm labor, and neonatal hypoglycemia. A positive correlation was observed between maternal BMI and adverse perinatal outcomes. Insulin-resistant women had higher rates of labor induction and cesarean deliveries compared to their non-resistant counterparts. Conclusion: Early screening for insulin resistance in pregnancy is crucial in peripheral setups. Timely diagnosis and appropriate management can significantly improve maternal and neonatal outcomes.